Analysis of Obata's Differential Equations on Pointwise Semislant Warped Product Submanifolds of Complex Space Forms via Ricci Curvature. (27th June 2021) - Ishan, Amira A.
Abstract : The present paper studies the applications of Obata's differential equations on the Ricci curvature of the pointwise semislant warped product submanifolds. More precisely, by analyzing Obata's differential equations on pointwise semislant warped product submanifolds, we demonstrate that, under certain conditions, the base of these submanifolds is isometric to a sphere. We also look at the effects of certain differential equations on pointwise semislant warped product submanifolds and show that the base is isometric to a special type of warped product under some geometric conditions.